Sanatorium pod Klepsydrą - Schulz, Bruno 1892-1942; Maksymiuk, Jerzy 1936- (DMMS-media distribution, 2013)
Set in pre-World War II Poland, a man visits the sanatorium where his father is dying and enters the surreal world where he relives some of his past and encounters strangeness at every turn